Soft Tissue Upper Lip Thickness in Different Skeletal Malocclusion Subjects -A Comparative Cephalometric Study - S.Abirami, Ravindra Kumar Jain (Institute of Medico-legal Publications Pvt Ltd, 2020)
The purpose of this study was to determine the soft tissue upper lip thickness of subjects with differentskeletal malocclusions. Lateral cephalograms of 30 patients ( control group : skeletal malocclusion I -10, Case group : skeletal malocclusion II - 10 , skeletal malocclusion III - 10 ) were selected randomlyfrom orthodontic records of subjects who reported to the Department of Orthodontics in Saveetha DentalCollege.All cephalograms were traced and upper lip thickness was measured using FACAD software.One way - ANOVA test was done, soft tissue upper lip thickness was found to be statistically significant(p<0.05) among different skeletal malocclusions. Post hoc test ( Tukey HSD ) was performed to find out thedifferences between each skeletal class , the upper lip thickness was found to be comparatively high in ClassIII compared to Class I and Class II (p<0.001). This study concluded that soft tissue upper lip thickness wasfound to be greater in skeletal class III malocclusion compared to other skeletal class I and II malocclusion.